Dynamic Security of Virtualized Systems: An Analysis of Time-based Impact - Hughes, Jerald (2012)
Virtualization technologies pose time-sensitive security challenges that need to be addressed from a dynamic security perspective. Adopting a dynamic security approach can help organizations manage the security risks inherent in virutalized environments. This paper conceptually examines current thought on best practices in information security systems which explains the dynamic nature of virtualized systems and paves the way for an information security model into which virtualization can be incorporated. We suggest that a proper analysis of timebased impact of security threats would help mitigate virtualization security risks, allowing IT security professionals and users to efficiently coordinate security objectives with the larger goals of the organization.